Spirit of Omotenashi which is expressed through Rikyuu Douka - Cicilia Tantri Suryawati; Listyaningsih Listyaningsih (Budapest International Research and Critics University, 2021)
In Chanoyu, Omotenashi, serving wholeheartedly begins when one thinks of carrying out chanoyu. It starts with making and sending invitations, preparing the venue and equipments, welcoming guests, and tidying it up again reflected real forms of omotenashi. Chanoyu, Sadou, or the way of Tea not only includes how to serve tea to guests and followed by the guests drink the tea, but it is full of teachings to serve and to live a harmonious life. This paper discusses omotenashi expressed in Rikyuu Douka. Rikyuu Douka is a teaching written by Sen no Rikyuu in the form of 100 pieces of waka on the procedure of preparing the tea room, treating equipments, and also things needed to be done both by the host and the guests. Of the 100 poems, 20 poems related to the procedure of serving the guests were examined. Using descriptive analysis methods and data sources taken from